Sound Wave Digital Learning Material Integrated Augmented Reality and CTL Model to Promote Students' 21st Century Skills - Jessica Alfa; Asrizal (Universitas Pendidikan Ganesha, 2023)
The learning process should be able to develop students' 21st century skills. In fact, students' 21st century skills are still low. Skills in the 21st century that need to be developed by students are 4C abilities, including: critical thinking and communication. The purpose of this research is to analyze the results of the needs analysis, the results of the validity test, and the results of the practicality test of digital learning materials to support the improvement of students' 21st century skills. The type of research used is R&D with the Hannafin and Peck model. The subjects in this study were students of class XI senior high school. The instruments used are questionnaires, test questions, and performance assessment to analyze student needs; product validation sheets to determine product validity; and product practicality sheets to determine the practicality of product use. The data analysis used in this research is descriptive statistical analysis. The validity test data analysis was conducted using Aiken's V formula. The validity analysis results show that the average validation value of AR-CTL digital learning materials is in the valid category. The practicality analysis value of AR-CTL digital learning material is in the practical category. So, it can be concluded that the augmented reality digital learning material integrated with the CTL model are valid and practical to promote students' 21st century skills.